Analysis of the mathematical reflective thinking ability of MTs students in terms of self-regulated learning during the COVID-19 pandemic - Kamalia, Millah; Nuriadin, Ishaq (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aims to analyze and describe students' mathematical reflective thinking abilities during online learning in terms of self-regulated learning during the COVID-19 pandemic. The method used is qualitative descriptive. The purposive sampling technique was used to select 3 samples consisting of 1 subject having high self-regulated learning, 1 subject having moderate self-regulated learning, and 1 subject having low self-regulated learning. The instrument in this research used a mathematical reflective thinking ability test and self-regulated learning questionnaires. Data analysis in this research uses the Miles and Huberman model, namely data reduction and categorization, data presentation, drawing conclusion, or verification. The triangulation technique is carried out by comparing the results of the mathematical reflective thinking test with interviews to verify the validity of the data. The conclusion of this research is that subject who have high self-regulated learning is quite reflective, the subject who have moderate self-regulated learning is quite reflective, and the subject who have low self-regulated learning is less reflective.